The critical role of hydroxyl groups in water vapor sensing of graphene oxide. Issue 4 (7th November 2018) - Fatima, Qawareer; Haidry, Azhar Ali; Yao, Zhengjun; He, Yue; Li, Zhong; Sun, Linchao; Xie, Lijuan
Abstract : The present study provides a significant conceptual advance in graphene oxide based humidity sensors. It is found that sensor response is directly dependent on the amount of OH − groups. The proposed strategy to control OH − in this report can make significant impact on the development of future smart GO-based humidity sensors and should be applicable to other gases. Abstract : Excellent adsorption of water vapor on the surface of graphene oxide (GO), which contains several inherited functional groups, leads to the development of improved humidity monitoring systems that can urgently meet the high industrial demand. In this study, we fabricated a GO-based humidity sensor and investigated the influence of hydroxyl group concentration on its performance. The sensor exhibited excellent humidity sensing performance in terms of sensitivity (sensor response ∼40 for 90% RH), selectivity, stability (both long-term and short-term) and reaction time ( τ res = 8.5 s and τ rec = 13 s). Additionally, this sensor does not require external power consumption for heating; thus, the aforementioned performance (recorded at room temperature) with an applied voltage of 0.1 V can significantly reduce the power/energy consumption to about ∼1.314 × 10 −4 kW h per year. In the future, this type of sensor can be integrated into smart humidity monitoring systems to not only monitor but also control the humidity levels on a specific application area. Based on complementary characterization techniques, such as XRD, AFM, Raman and electrical measurement, here, we propose a physical-chemical sensing model to elucidate the aforementioned sensor characteristics.